Classical Rhetorical Analysis on Paul’s Character in His Speech at Miletus (Acts 20:18–35) - Christopher, Dany (Sekolah Tinggi Teologi SAAT, 2021)
In his speech at Miletus (Acts 20:18–25), Paul talks about himself repeatedly. Such emphasis on the character of Paul inevitably raises some questions regarding the function of the emphasis. This article attempts to understand the function of the emphasis on the character of Paul in the Miletus speech. The method used to analyze the speech is the classical rhetorical method. Classical rhetoric follows the convention of ancient Greco-Roman rhetoric to examine how a speech persuades the audience to act according to what the speaker intends. In studying the Miletus speech, the author will investigate several elements from classical rhetoric, such as the rhetorical invention, with particular discussion to ethos (character), pathos (emotion), and logos (the logic of the argumentation), the rhetorical species, the rhetorical arrangement, and the rhetorical effectiveness. The main argument of this article is that the emphasis on Paul’s character functions as the basis for the accountability of Paul’s ministry and the basis for his exhortation to the elders of the Ephesian church.